(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
In folklore studies, it is a proven scientific fact that the subject of epic works is formed by the interaction of motives. In the study of each motif, other motifs related to it will undoubtedly be mentioned. In particular, the study of the essence of the travel motive begins with the issues of connection with the factors that create it. This article talks about the role of prohibition in the fairy tale and its importance in organizing the hero’s journey.